2009
DOI: 10.1348/014466608x354580
|View full text |Cite
|
Sign up to set email alerts
|

The effects of private and collective self‐priming on visual search: Taking advantage of organized contextual stimuli

Abstract: Two experiments tested the hypothesis that priming the collective self improves some visual search tasks. In both experiments, participants searched for an O among Qs. The pattern of distracters was manipulated across experiments to allow the possibility of grouping (Experiment 1) or to disallow this possibility (Experiment 2). Consistent with expectations, collective self-priming increased visual search speed when grouping was possible but it had no effect on visual search speed when grouping was not possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 69 publications
(142 reference statements)
0
12
0
Order By: Relevance
“…4;2013 13 reputations, or resources later", the self is limited to the individual. For the theme "Our community is more advanced than other communities", the self is extended to the community, sometimes called a collective self-construal (e.g., Rice, Clayton, Trafimow, Keller, & Hughes, 2009). Finally, for the theme "The world is gradually progressing or could improve dramatically in the future", the self is extended to all humanity, analogous to the concept of humanity esteem (Luke & Maio, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…4;2013 13 reputations, or resources later", the self is limited to the individual. For the theme "Our community is more advanced than other communities", the self is extended to the community, sometimes called a collective self-construal (e.g., Rice, Clayton, Trafimow, Keller, & Hughes, 2009). Finally, for the theme "The world is gradually progressing or could improve dramatically in the future", the self is extended to all humanity, analogous to the concept of humanity esteem (Luke & Maio, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The individual and collective priming conditions added a description of how his decision benefitted either his own self-interest or his family's interest, respectively (see [4]). Next, participants listed five benefits of the warrior's decision (in the individual and collective conditions) or five events from their day (in the neutral control condition), taken from Rice et al [11]. The purpose of this was to increase the strength of the priming effect and to make sure that the participant read the prime (see Appendix S1).…”
Section: Methodsmentioning
confidence: 99%
“…Recent research has demonstrated self-construal priming effects in visual search behavior [11], [12] and visual pattern recognition [13]. Oyserman et al [13], [ see also 14] demonstrated that priming individual or collective self-construals results in differential processing of both visual and auditory stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Self-construal is conceptualized as individuals' belief and behavior regarding their relationship with others and the self that is distinct from others [103]. Different self-construals can lead to variations in personal thoughts and information processing [93,112]. For example, research has found that self-construal priming can affect an individual's decision-making [126], self-esteem [44] and visual search speed [93].…”
Section: Treatmentsmentioning
confidence: 99%
“…Trafimow and colleagues showed that self-construal could be primed by asking individuals to think about a question [112,126], by reading a story [93,112] or by using a specific language [62,111]. We adopted a priming method that has been used in previous studies (e.g., [112,126]).…”
Section: Treatmentsmentioning
confidence: 99%